Enhancing Reading Comprehension: The Role of RCRR Strategy and Small Group Discussions - Rahmadianti, Dwi; Flora, Flora; Munifatullah, Feni (Universitas PGRI Sumatera Barat, 2025)
This study addresses the ongoing challenge of improving students' reading comprehension, which is crucial for academic success. Despite various reading strategies being implemented, discrepancies remain between theoretical approaches and classroom practices, particularly in engaging students actively in comprehension tasks. To bridge this gap, this study examines the effectiveness of integrating the Read, Cover, Remember, Retell (RCRR) strategy with Small Group Discussions in enhancing students’ comprehension of descriptive texts. Conducted at SMA N 10 Bandar Lampung, this quasi-experimental research involved tenth-grade students, utilizing a pretest-posttest design with 42 multiple-choice questions. The experimental group, exposed to the integrated strategy, showed a significant improvement in reading comprehension, with a post-test mean score of 85.99, compared to the control group’s 76.53. Statistical analyses, including normality, homogeneity, and independent t-tests, confirmed the strategy’s effectiveness (p < 0.05). Findings indicate that Small Group Discussions enhanced the impact of RCRR by fostering active engagement, critical thinking, and collaborative learning. This study concludes that combining RCRR with Small Group Discussions is an effective instructional approach, providing valuable insights for educators seeking to enhance literacy instruction.